1970
DOI: 10.5424/sjar/2010084-1405
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial diversity of the occurrence of atmospheric drought in Poland (1966-2005) and its effect of yield of pickling cucumber (Cucumis sativus L.)

Abstract: Counteracting the negative effects of drought in vegetal production should include drought monitoring, determination of drought tolerance and, thus, the assessment of risk, limitations and losses of yield for various species of cultivated plants. The aim of the work was to assess temporal and spatial variability of the occurrence of atmospheric drought in Poland and to determine the risk of cultivation of pickling cucumber caused by this phenomenon. To carry out the task, starting data concerning the marketabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
(41 reference statements)
3
19
0
Order By: Relevance
“…Similar results were obtained while analysing frost occurrence in different areas of Poland, among others, in Szczecin Lowland [26], in the area of Bydgoszcz [16], in North-Eastern Poland [22] and in Poland as a whole [20,27]. Schein ger et al [15] while analysing the occurrence of last frosts in spring in Central Europe between 1951 and 1997, also showed that it occurred increasingly early, at a rate of 0.2 day·year − .…”
Section: Discussion Of Resultssupporting
confidence: 66%
“…Similar results were obtained while analysing frost occurrence in different areas of Poland, among others, in Szczecin Lowland [26], in the area of Bydgoszcz [16], in North-Eastern Poland [22] and in Poland as a whole [20,27]. Schein ger et al [15] while analysing the occurrence of last frosts in spring in Central Europe between 1951 and 1997, also showed that it occurred increasingly early, at a rate of 0.2 day·year − .…”
Section: Discussion Of Resultssupporting
confidence: 66%
“…Dry periods are related to the atmospheric circulation patterns and can affect large areas . In temperate and boreal climates the effect of water shortage on vegetation is not as significant as in arid or semiarid areas, but there is strong evidence of water deficit effect on various types of vegetation in the study area (Kulikauskas and Sprainaitiene, 2005;Vitas and Erlickyte, 2008;Ozolincius et al, 2009;Kalbarczyk, 2010;Bijak, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the scientific investigations are concentrated on the spatial and temporal distribution of droughts (Hisdal et al 2001;Loyd-Hughes, Saunders 2002; and on the impact of droughts on hydrological cycles (Bordi et al 2009;Wilson et al 2010;Tallaksen et al 2011). Droughts are analyzed in a very wide context of scientific researches: drought impact on agro-ecosystems (Sakalauskaitė 2006;Schindler et al 2007;Kalbarczyk 2010;Rad, Zandi 2012) and on forest life (Maracchi et al 2005;Lindner et al 2007;MacKay et al 2012); interactions with water bodies (Peters et al 2006;Jakimavičius, Kovalenkovienė 2010;Hän-ninen, Vuorinen 2011) and water quality (Sakalauskiene, Ignatavicius 2003;van Vliet, Zwolsman 2008;Zielinski et al 2009). Palaeoclimatological drought conditions are discovered using sediments (Dippner, Voss 2004) and tree rings (Vitas, Erlickytė 2008;Bünt-gen et al 2010;Drobyshev et al 2011) data analysis.…”
Section: Introductionmentioning
confidence: 99%